2009
DOI: 10.1111/j.1365-2966.2009.14886.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranight polarization variability in radio-loud and radio-quiet AGN

Abstract: Intranight polarization variability in active galactic nuclei (AGN) has not been studied extensively so far. Studying the variability in polarization makes it possible to distinguish between different emission mechanisms. Thus, it can help answering the question if intranight variability in radio-loud and radio-quiet AGN is of the same or of fundamentally different origin. In this paper, we investigate intranight polarization variability in AGN. Our sample consists of 28 AGN at low to moderate redshifts (0.048… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…We then computed P Q and P U using standard formulae (e.g. Villforth et al 2009). In this phase, we checked that there were no spurious objects inside the measurement aperture.…”
Section: Discussionmentioning
confidence: 99%
“…We then computed P Q and P U using standard formulae (e.g. Villforth et al 2009). In this phase, we checked that there were no spurious objects inside the measurement aperture.…”
Section: Discussionmentioning
confidence: 99%
“…Variability of AGN polarization is well-known in the cm/radio regime (e.g., Aller et al 1985) and has been probed in the mm/radio regime for a few selected sources (e.g., Jorstad et al 2005) as well as in the optical (e.g., Villforth et al 2009). Our variability analysis (see Eqs.…”
Section: Variabilitymentioning
confidence: 99%
“…Sillanpaa et al (1991), based on the observations carried over six nights, found anticorrelation between flux and polarization variations which they explained as a result of highly rotating plasma inside a relativistic jet. However, Villforth et al (2009) did not find any clear correlation between flux and polarization. From long term (year time scale) photopolarimetric observations, Efimov et al (2002) noticed rapid continuous rotation of the position angle of about 4.92 degrees/day in clockwise direction suggesting a helical magnetic field jet structure.…”
Section: Introductionmentioning
confidence: 68%
“…Intra-night polarization variability (INPV) of OJ 287 has been studied earlier by Villforth et al (2009) who found about 16 % polarization. On the nights of 05, 06 and 10 April 2016, we have sufficient data points in R-band to characterize the INPV of OJ 287.…”
Section: Polarization Variabilitymentioning
confidence: 95%
See 1 more Smart Citation